Effects of bedtime very low dose cyclobenzaprine on symptoms and sleep physiology in patients with fibromyalgia syndrome: a double-blind randomized placebo-controlled study - Moldofsky, Harvey; Harris, Herbert W; Archambault, W Tad; Kwong, Terence; Lederman, Seth (Journal of rheumatology, 2011)
To determine the effects of bedtime very low dose (VLD) cyclobenzaprine (CBP) on symptoms and sleep physiology of patients with fibromyalgia (FM), unrefreshing sleep, and the α-nonREM sleep electroencephalographic (EEG) anomaly at screening. Of 37 patients with FM in the screened population, 36 were randomized and treated in this 8-week, double-blind, placebo-controlled, dose-escalating study of VLD CBP 1-4 mg at bedtime. We evaluated changes in subjective symptoms including pain, tenderness, fatigue, mood [Hospital Anxiety and Depression Scale (HAD)], and objective EEG sleep physiology (at screening, baseline, and Weeks 2, 4, and 8). In the VLD CBP-treated group (n = 18) over 8 weeks, musculoskeletal pain and fatigue decreased, tenderness improved; total HAD score and the HAD depression subscore decreased; patient-rated and clinician-rated fatigue improved. In the placebo-treated group (n = 18), none of these outcome measures changed significantly. Compared to placebo at 8 weeks, VLD CBP significantly improved pain, tenderness, and the HAD Depression subscore. Analysis of cyclic alternating pattern (CAP) sleep EEG revealed that significantly more subjects in the VLD CBP group than the placebo group had increased nights of restorative sleep in which CAP(A2+A3)/CAP(A1+A2+A3) = CAP(A2+A3(Norm)) ≤ 33%. For VLD CBP-treated subjects, the increase in nights with CAP(A2+A3(Norm)) ≤ 33% was correlated to improvements in fatigue, total HAD score, and HAD depression score. Bedtime VLD CBP treatment improved core FM symptoms. Nights with CAP(A2+A3(Norm)) ≤ 33% may provide a biomarker for assessing treatment effects on nonrestorative sleep and associated fatigue and mood symptoms in persons with FM.